Destruction and removal of microorganisms from food equipment and utensil surface by detergent. II. Staphylococcus aureus - Mabesa, R.C; Contreras, E.A; Castillo, M.M; Banaad, L.; Bandia, V. (1982)
The destruction and removal of staphylococcus aureus by selected locally available detergents from various food equipment and utensil surfaces were studied. Sample plates of stainless steel, aluminum, cast and iron-aluminum and plastic were artificially soiled with, milk containing viable cells of S. Aureus and washed with different preparation at 20degressC., 30degreesC, and 40degreesC for 1,5 and q0 minutes. A standardized and simulated washing technique was employed. Statistical analysis showed no significant difference in the cleaning ability of the detergents tested and between the range of temperatures of detergent solutions used. Plastic and stainless surfaces seem to clean easily, better than aluminum and cast iron-aluminum surfaces although data revealed no significant differences. A longer time of detergent exposure is required for higher bacterial destruction and removal